Typification of the Linnaean name Rhamnus tinctoria, the basionym of Flueggea tinctoria (Euphorbiaceae), an endemic plant to the Iberian Peninsula flora - Ferrer-Gallego, Pedro Pablo (UMA Editorial, 2025)
The name Rhamnus tinctoria was published in 1758 by Linnaeus in Loefling’s Iter Hispanicum. The work was published posthumously after Loefling’s death in Venezuela in 1756. Although Linnaeus received specimens from Loefling’s Iberian collections, several were lost, so Linnaeus relied on Loefling’s notes for these taxa. Since it was impossible to find original material of Rhamnus tinctoria in the various Linnaean and Linnaean-associated herbaria, a neotype has been designated for this Linnaean name. The neotype selected is a specimen preserved at MA, collected in central Spain (Talavera de la Reina, Toledo). This specimen belongs to the exsiccatum “E. Bourgeau. Plantes d’Espagne” (number 2492), which contains several duplicates (e.g., at P, barcodes P05595291, P05503187, P05502243).

El nombre Rhamnus tinctoria fue publicado en 1758 por Linneo en el Iter Hispanicum de Loefling. La obra fue publicada póstumamente tras la muerte de Loefling en Venezuela en 1756. Aunque Linneo recibió ejemplares de las colecciones ibéricas de Loefling, varios de ellos se perdieron, por lo que Linneo se basó en las notas de Loefling para estos táxones. Dado que fue imposible encontrar material original de Rhamnus tinctoria en los diversos herbarios de Linneo que se han consultado, se ha designado un neotipo para este nombre. El neotipo seleccionado es un ejemplar conservado en MA, recolectado en el centro de España (Talavera de la Reina, Toledo), que pertenece al exsiccatum “E. Bourgeau. Plantes d’Espagne” (número 2492), que contiene varios duplicados (por ejemplo, en P, códigos de barras P05595291, P05503187, P05502243).
Keywords: Plantas - Clasificación; Fitogeografía; Iter Hispanicum; Loefling; Linnaeus; Neotipo; Nomenclatura; España; Tamujo